CYCLES OF SOLAR ACTIVITY AS A BASIS FOR FORECASTING THE QUALITY OF DNIEPER WATER - Kulishenko, Oleksiy; Klymenko, Natalia (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
One of the main features of the quality of the Dnieper water is the content of natural organic substances which determine the water oxidizability and color indexes. A special problem is that organic substances are poorly removed by water treatment plants. A significant problem in the operation of water treatment plants is the unpredictability of annual changes in the quality of Dnieper water, which complicates logistics management, for example, the supply of reagents. Many years of experience related to the Dnieper water supply station in Kyiv (DnWS) have led to the hypothesis that these changes are in some way related to the cycles of solar activity. The purpose of this work is to test this hypothesis to substantiate the possibility of predicting the quality of Dnieper water depending on the action of such a global factor as solar activity. The work was performed by statistical methods using 60-year results of Dnieper water analyzes provided by the DnWS laboratory, as well as Wolf numbers (Sunspot Numbers) provided for free use by the Royal Observatory of Belgium. The influence of solar activity on the quality indicators of Dnieper water, especially in its peak and post-peak periods, has been statistically confirmed. The interaction of biological and physicochemical parameters as factors influencing water quality is shown. Conclusions. As a result of the construction of six reservoirs in 1931-1976, the Dnieper from the river actually turned into a network of water bodies. Now these reservoirs are a kind of reactors in which water is treated by electromagnetic solar radiation, which leads to the cyclic transformation of phytoplankton and natural organic matter. Taking into account the cycles of solar activity, the logistical planning of the operation of water treatment facilities receives an independent "base", changes in which can be predicted with some reliability for years to come.